ANALISIS DAYA DUKUNG AKSIAL TIANG GRUP AKIBAT PERGESERAN AS-SPUN PILE - Immanuel Panusunan Tua Panggabean; Valentana Ardian Tarigan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
The construction of bridge and dock abutments generally uses pile foundations, the use of pile foundation is carried out to prevent erosion or movement of land on the surface which can result in loss of bearing capacity or a significant reduction in bearing capacity if carried out using a shallow foundation. The implementation of the pile foundation construction also often experiences a shift in its axle position so it needs to be reviewed the carrying capacity that occurs due to the shift of the axle carrying capacity of the plan. Analysis due to shifting of as-spun pile using the Feld method approach and the Converse-Laberre method as a review of spun pile group bearing capacity efficiency. The bearing capacity of the group pile in the existing condition decreased due to the shift of the pile as far as 1 (one) meter, but it was still within safe limits to carry the burden of the plan.